IMPLEMENTATION OF MADRASAH HEAD SUPERVISION IN TSANAWIYAH MADRASAH (MTS) STORED AT THE MINISTRY OF RELIGION IN TANJUNGBALAI CITY - Faisal, Faisal; Arsyad, Junaidi; Nahar, Syamsu (UIN Sumatera Utara Medan, 2023)
This research aims to reveal the implementation of Supervision of Madrasah Heads in Assisted Madrasah Tsanawiyah (MTs) in the Ministry of Religion of Tanjungbalai City, how academic supervision techniques are carried out by Madrasah Heads as well as supporting and inhibiting factors in the implementation of academic supervision of Madrasah Heads in Assisted Madrasah Tsanawiyah (MTs). At the Ministry of Religion of Tanjungbalai City. The method used is a qualitative type, with a phenomenological approach, research data collection was obtained using triangulation techniques with data collection techniques from documents, interviews and observations. The results of this research reveal three findings that the implementation of academic supervision carried out by the Head of the Madrasah at the Madrasah Tsanawiyah (MTs) under the guidance of the Ministry of Religion of Tanjungbalai City is correct and follows existing procedures but the implementation is not optimal because there are still obstacles in its implementation such as facilities and infrastructure and other.